2016
DOI: 10.1093/mnras/stw258
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Shape of the Milky Way Disk and Halo from M-type Brown Dwarfs in the BoRG Survey

Abstract: We have identified 274 M-type Brown Dwarfs in the Hubble Space Telescope's Wide Field Camera 3 (WFC3) pure parallel fields from the Brightest of Reionizing Galaxies (BoRG) survey for high redshift galaxies. These are near-infrared observations with multiple lines-of-sight out of our Milky Way. Using these observed M-type Brown Dwarfs we fitted a Galactic disk and halo model with a Markov chain Monte Carlo (MCMC) analysis. This model worked best with the scale length of the disk fixed at h = 2.6 kpc. For the sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…component well above the plane of the disk, i.e., we are including the density of Halo stars in our disk fit. A 0.1 dex offset suggest of order 10% of the stars in are, in fact, Halo stars (see also van Vledder et al 2016). The values in Figure 27 and Table 10 are still too high to be consistent with previous work on the vertical scale of stars in the thin disk.…”
Section: Future Worksupporting
confidence: 74%
“…component well above the plane of the disk, i.e., we are including the density of Halo stars in our disk fit. A 0.1 dex offset suggest of order 10% of the stars in are, in fact, Halo stars (see also van Vledder et al 2016). The values in Figure 27 and Table 10 are still too high to be consistent with previous work on the vertical scale of stars in the thin disk.…”
Section: Future Worksupporting
confidence: 74%
“…While both haloes are richly substructured and qualitatively agree with the ΛCDM paradigm of galaxy formation, they display significant differences. The Milky Way halo has a weak to no metallicity gradient (Sesar et al 2011;Xue et al 2015) and its stellar density distribution can be described by a broken power-law -within 25 − 30 kpc, it follows an oblate, ρ ∝ r −γ powerlaw distribution with index γ ∼ 2.5 − 3 (Yanny et al 2000;Bell et al 2008;Jurić et al 2008;van Vledder et al 2016) whereas a more rapidly declining stellar density is detected beyond ∼ 30 kpc, with γ ∼ 3.5 (Deason et al 2011;Sesar et al 2011;Deason et al 2014;Cohen et al 2015;Slater et al 2016). M31, on the other hand, has a clear metallicity gradient with a 1 dex variation in [Fe/H] from 10 to ∼100 kpc (Gilbert et al 2014;Ibata et al 2014) and its stellar density distribution can be described by a single power-law with γ ∼ 3.3 (Guhathakurta et al 2005;Gilbert et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a search for the lowest-mass substellar objects belonging to the Milky Way can benefit from observations such as the above default parallels. The randomized sampling of the Milky Way volume equally benefits constraints on the shape of the Milky Way (Pirzkal et al 2005(Pirzkal et al , 2009Ryan et al 2005Ryan et al , 2011Ryan et al , 2017Holwerda et al 2014Holwerda et al , 2018van Vledder et al 2016). The near-infrared observations of JWST are sensitive to Figure 1.…”
Section: Science Case B: Brown Dwarf Population Of the Milky Waymentioning
confidence: 99%
“…The WFC3 Infrared Spectroscopic Parallel Survey (WISP) default parallel grism survey with HST/WFC3 (Atek et al 2010) has successfully characterized the intermediate-redshift population (e.g., Atek et al 2011Atek et al , 2014Bedregal et al 2013;Malkan & WISP Team 2013), predicted more use of grism spectroscopy in NIR surveys (Colbert et al 2013), and identified some Milky Way halo objects (Masters et al 2012). Grism observations also hold the potential to cleanly separate AGN and star formation contributions in intermediate-redshift galaxy populations (Trump et al 2011;Bridge et al 2016).…”
Section: Science Case F: Grism Observationsmentioning
confidence: 99%